Evaluación del plan haccp en una planta procesadora y exportadora de camarón en la provincia de El Oro - Cevallos Galarza, Byron Francisco (Machala : Universidad Técnica de Machala, 2012)
Los aspectos más relevantes a tener en cuenta tanto consumidores como operadores de empresas alimentarias incluso administraciones públicas son la calidad y seguridad alimentaria. Es por esto que existen al respecto en la actualidad gran cantidad de normativas que comprenden desde higiene de productos alimenticios, la comercialización de determinados productos hasta los requisitos técnicos sanitarios, condiciones de transporte de productos alimenticios sin dejar de lado la relativa a parámetros físico químicos microbiológicos y organolépticos entre otros, que deben ser respetados por empresas alimenticias. La idoneidad de este sistema HACCP está fundamentada en una serie de principios básicos dentro de los cuales se determina la necesidad de establecer procedimientos para verificar que este sistema esté funcionando correctamente. Con base en esto es importante que nuestro país mantenga esta reputación a nivel internacional controlando y evaluando constantemente los procedimientos aplicados a este recurso durante la fase de proceso en planta que es donde existen probabilidades de contaminación, es así que como trabajo de titulación me he propuesto desarrollar esta investigación que tiene como objetivo general el siguiente punto. El objetivo principal de esta investigación fue evaluar el Plan HACCP en una planta procesadora y exportadora de camarón en la provincia de El Oro. Lo más importante del sistema de verificación regulatoria es llevar a cabo inspecciones, auditorias, verificaciones de acuerdo a un plan establecido para determinar si los estándares, especificaciones y sistemas basados en manejo de riesgos se encuentran en conformidad; determinar la validez continua de sistemas de manejo de riesgos de una manera verificable; requerir acciones correctivas en caso de no conformidades.
The most important aspects to consider both consumers and food business operators including public administrations are quality and food safety. That is why there are now about lots of regulations ranging from food hygiene, the marketing of certain products to the healthcare technical requirements, conditions of transportation of food products without neglecting the physical and chemical parameters on microbiological and organoleptic among others, which must be respected by food companies. The adequacy of the HACCP system is based on a se-ries of basic principles within which determines the need to establish procedures to verify that the system is working properly. On this basis it is important that our country maintains its reputation internationally constantly monitoring and assessing the procedures applied to this resource during the process plant where there is likelihood of contamination, so as graduation work I have proposed develop this research has the general objective the next point. The main objective of this research was to evaluate the HACCP Plan in a processing plant and export of shrimp in the province of El Oro The most important regulatory system verification is to con-duct inspections, audits, inspections according to a plan for determine whether the standards, specifications and systems based on risk management are in compliance, to determine the continuing validity of risk management systems in a verifiable, require corrective action in case of non-conformities. Validation activities may be similar, in terms of scope and time commitment to the development of HACCP plan original. Validation should be performed within the plant initially, before really trust the HACCP plan and when factors warrant. These factors could include: changes in raw materials, product or process, adverse findings in the review; deviations recurrent new scientific information on potential hazards and control measures; comments online, or new distribution practices or consumer handling . The primary role of regulators in a HACCP system is to verify that HACCP plans are effective and being implemented. Verification procedures of an agency include a review of the HACCP plan and any amendments, review of monitoring records for CCPs, review of records of corrective ac-tions, review of records of verification, visual inspections of operations to determine if is fol-lowing the HACCP plan and records are being properly. Once the final audit could conclude that the company under study has a rating of 100 % which corresponds to compliance. Recommendations regarding the School and the School of Aquaculture specifically offered to staff and students greater teacher-student training in the area of quality control. It is necessary for companies engaged in the handling, processing and export of shrimp, train your staff pe-riodically skilled labor that corresponds to GMP - SSOP HACCP based, as well as getting the most out HR the link University - Industry since this offers all the facilities to the student with various facilities and equipment.
Keywords: PLANTA; PROCESADORA; CAMARÓN